2014
DOI: 10.1002/hed.23587
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid autoimmunity and risk of malignancy in thyroid nodules submitted to fine‐needle aspiration cytology

Abstract: Thyroid nodule malignancy in patients with Hashimoto thyroiditis is not more frequent than in patients without thyroiditis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
25
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 19 publications
1
25
0
1
Order By: Relevance
“…Our results are in agreement with some studies [29,32], while others report no difference in thyroid cancer prevalence between single nodules and multinodular goiter [33,34,35]. A recent meta-analysis reported that thyroid cancer is less frequent in multinodular goiter than in single nodules, particularlyoutside the USA and perhaps in iodine-deficient areas [36].…”
Section: Discussionsupporting
confidence: 82%
“…Our results are in agreement with some studies [29,32], while others report no difference in thyroid cancer prevalence between single nodules and multinodular goiter [33,34,35]. A recent meta-analysis reported that thyroid cancer is less frequent in multinodular goiter than in single nodules, particularlyoutside the USA and perhaps in iodine-deficient areas [36].…”
Section: Discussionsupporting
confidence: 82%
“…As mentioned earlier, Kim et al were the first to report that a positive TgAb test was an independent predictor of thyroid nodule malignancy, regardless of the presence of CLT. A more recent study conducted by Grani et al showed that an isolated TgAb positivity could be a mild risk factor for thyroid cancer, as opposed to Hashimoto's thyroiditis, which did not correlate positively with malignant pathology [13].…”
Section: Discussionmentioning
confidence: 93%
“…In the aforementioned studies by Kim et al [11] and Grani et al [13], the patient's final diagnostic outcome was established following FNAC, with only a minority of diagnoses confirmed by histological follow-up. One limitation of using FNAC as a diagnostic tool is that the cytological features observed in the sample obtained are not necessarily representative of the entire thyroid tissue and cannot consequently offer a definitive diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…При цьому вивчення асоціації супутньої тиреоїдної патології та злоякісних пухлин стосувалося і стосується майже виключно папілярної карциноми (ПК) і, в більшості випадків, впливу хронічного тиреоїдиту на її виникнення та формування агресивності [1][2][3][4][5]. Однак і ця інформація часто є супе-речливою, бо за одними даними наявність супутнього тиреоїдиту є сприятливим чин-ником перебігу онкологічного захворювання [6][7][8], за іншими -пухлина на тлі хронічного автоімунного тиреоїдиту проявляє лише окре-мі сприятливі властивості [9] чи біологічні характеристики ПК і перебіг захворювання не залежать від наявності тиреоїдиту, який не має ніякого впливу на прогресування зло-якісної пухлини ЩЗ [5,[10][11][12][13][14][15]. Існують також дані, що ПК може мати гірший клінічний перебіг у певної частини хворих з хронічним тиреоїдитом [16] чи ефект останнього зале-жить від тяжкості його перебігу [17].…”
unclassified